The development of a favourable ecosystem for private equity firms in Myanmar - Ramos-Romanow, Pauline Marie Madeleine (2020)
The aim of this Master’s Degree thesis is to study the development process of the Private Equity industry in Myanmar considering the major institutional factors that are at play in the so-called ‘frontier markets’. The final aim is to elaborate a framework providing an understanding of Private Equity development and deals in Frontiers markets, arguing that institutional factors have a strong influence in this process. Given that Myanmar has been initiating a gradual liberalization of its economy for less than a decade, this sector is still at a very nascent stage, and new developments and reforms are happening almost very frequently. This particular context will therefore enable us to have a privileged, immediate and up-to-date exposure in order to understand the development process of Private Equity funds in frontiers markets. Using the theoretical framework of the Institutional Theory and adopting a qualitative research methodology, this paper will study how the creation of local ecosystem has been influencing the development of the Private Equity industry in the country. As such, this work will first focus on the role of institutions in shaping an environment, that had a positive and negative influence over the development process of the local Private Equity industry. Then, it will assess how the funds adapted to this landscape and behave into this ecosystem. Combining these findings will allow us to develop a framework describing the ‘enabling ecosystem’ conducive for private equity development. Our methodology will enable us to empirically validate and the existing literature on the drivers of PE. However, our analysis seeks to have a broader ambition: drawing from those findings, we will argue that the development of the Private Equity industry depends on the creation of a favourable ecosystem resulting from the interplay of various actors and factors.